2017
DOI: 10.1002/jclp.22495
|View full text |Cite
|
Sign up to set email alerts
|

Black and White Parents’ Willingness to Seek Help for Children's Internalizing and Externalizing Symptoms

Abstract: Objective: Understanding social and environmental factors that contribute to parental help-seeking intentions is an important step in addressing service underutilization for children in need of treatment. This study examined factors that contribute to parents' intentions to seek formal and informal help for child psychopathology (anxiety and attention-deficit/hyperactivity disorder [ADHD]). Method: A total of 251 parents (N = 128 mothers, N = 123 fathers; 49% Black, 51% White) read 3 vignettes describing child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 59 publications
1
11
0
Order By: Relevance
“…38 In addition, studies have documented that Black cultural values of personal strength and addressing problems within the family or through religious practices may view seeking professional help for mental health problems as a sign of weakness. [39][40][41][42][43] Several structural health system factors are known barriers to Blacks receiving behavioral health care. First, historical racism that is embedded in medical research and clinical treatment has contributed to mistrust of providers and the mental health system.…”
Section: Discussionmentioning
confidence: 99%
“…38 In addition, studies have documented that Black cultural values of personal strength and addressing problems within the family or through religious practices may view seeking professional help for mental health problems as a sign of weakness. [39][40][41][42][43] Several structural health system factors are known barriers to Blacks receiving behavioral health care. First, historical racism that is embedded in medical research and clinical treatment has contributed to mistrust of providers and the mental health system.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has suggested, especially among non-native parents, limited and difficult access to healthcare facilities. 20 66 Longitudinal and experimental studies are recommended to examine the differential pathways between parent–perceived versus diagnosed child psychosocial problems and the use of healthcare. Environment factors, including health care system and external environment, should be studied as contemplated by the Andersen model; taking into account access parents have to healthcare, but also barriers they perceive to make use of healthcare.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that predisposing factors, such as child’s ethnic background and gender, are associated with parental help-seeking. 20 21 Enabling factors, such as higher parental educational levels and higher incomes, have been shown to positively encourage parents to seek help for their child’s problem behaviour (4–14 years old). 22 23 An important need factor that has been reported to increase help-seeking by parents is recognition of the child’s problem (6–11 years old).…”
Section: Introductionmentioning
confidence: 99%
“…Particularly for Black parents, the church may play an important role in encouraging parents to seek mental health services for their child for both internalizing and externalizing problems. Previous research has demonstrated that Black adults more often turn to religious institutions for personal support than White adults (Thurston et al, 2018). Since Black populations are more likely to look to church leaders for support, it is crucial for clinicians to encourage clergy and other trusted agents at faith communities and religious jurisdictional bodies to make mental health care more accessible to Black families.…”
Section: Strategies For Increasing Mental Health Utilization In Black...mentioning
confidence: 99%